MENGAWAL REGENERASI MEMBANGUN BUMI PERTIWI (MEMBUMI) STUDI KASUS: SENTRA GERABAH BANJAR BINOH, DESA UBUNG-DENPASAR - PUTU SURYA TRIANA DEWI; I WAYAN YOGIK ADNYANA PUTRA (GANEC SWARA, 2023)
Pottery, a craft full of stories that may be forgotten. Pottery is one of the oldest markers of the guardians of civilization in the archipelago. Based on the results of research by archaeologists in several places in Bali, traces of pottery in the form of small stupas, clay materials, and pots believed to be grave supplies were found, proving that the ancient Balinese people were familiar with the ceramics that made from clay, and Binoh was one of the pottery centers in Bali in the past. Regeneration is the biggest problem they face, the average age of craftsmen is already in the elderly phase. Regeneration becomes difficult because the younger generation, who prefers to work in an office, is reluctant to 'work using soil that looks dirty'. This research focuses on studying further the perception of local youth about pottery craftsmen in order to produce the most appropriate persuasive approach strategy for the younger generation. Fundamental knowledge of the characteristics of materials and pottery technique will be the basis for exploration to innovate. This research is important to be done immediately considering the absence of regeneration in craftsmen. The data collection method uses a rational-empirical approach (inductive qualitative), the problem is studied theoretically to find basic of rationality. The output of this research is expected to be able to find an effective educational program for the regeneration of pottery craftsmen to maintain the sustainability of the economic potential of pottery in Banjar Binoh, Ubung Kaja Village, Denpasar